Hierarchical analysis of the prevalent essay writing errors among major English students - Hamarai, Faiz; Ahmed, Abdalla (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to investigate the common errors made by Saudi EFL major students in essay writing and identify the possible sources of these recurring errors. By examining the specific linguistic challenges faced by these students, the study provides insights into the underlying factors affecting their writing proficiency. A total of thirty essays written by thirty English major students were analyzed. The students were divided statistically into two groups using hierarchical cluster analysis (HCA), and their essays were assessed for various types of errors, including syntax, cohesion, grammar, and punctuation. A comparative analysis was conducted to determine the frequency and distribution of these errors across the two groups. The results indicate that syntax-related errors are the most prevalent, whereas cohesion-related errors occur the least frequently. Notably, the first group accounted for 77% of the total errors, while the second group contributed 23%, highlighting a significant discrepancy in writing proficiency. The findings suggest that students struggle primarily with sentence structure, grammar, and punctuation, which adversely affect their writing quality. Based on these insights, the study recommends the implementation of targeted remedial programs to address these issues and enhance students’ overall writing proficiency, ultimately leading to improved academic performance in English.